Scarcity of pain medication in Pakistan following the devaluation of currency - Shabbir, Muhammad Bilal; Zahoor, Shaghaf; Ilyas, Danial (Journal of the Pakistan Medical Association, 2023)
Madam, The scarcity of drugs harms patient safety and care.1 Media publications on the shortage of painkillers tend to generate panic and anxiety among the public owing to their role in patient analgesia and recovery. Pain, especially when untreated, has far-reaching consequences for patients' quality of life, including psychological, physical, social, and economic consequences. Untreated pain has proven to be associated with depression, mood fluctuations, and emotional instability, resulting in an overall low quality of life. The shortage of medicines is common globally, and the causes are multifaceted depending upon the region in consideration. Currently, Pakistan is in a similar crisis where the decreased availability of medications, among which analgesics constitute a vast proportion, is leaving many holes in quality, patient management and care protocols2-3 The reasons for the current crisis are multifactorial. However, the major chunk of it lies in the devaluation of the currency and the skyrocketing prices of petroleum, which has caused inflation among all utilities, including medicine. Reports by media outlets have shown an 80% increase in prices compared to prices five years prior. In contrast, the Pakistan Pharmaceutical Manufacturers Association (PPMA) chairman claimed only a 21–30% price increase. The gravity of the situation can be further augmented by the fact that the cost of paracetamol was increased from Rs 600/kg to Rs 2600/kg earlier this year, yet the medicine remains unavailable in the market.4 The scarcity of medication is not limited to pharmacies but has also found its way to hospitals, where the healthcare providers either have to prioritize patients when it comes to giving analgesia or there is no analgesia available in smaller setups.5 Another factor contributing to this predicament is the climate change-induced floods in the country. There is an increased demand for medicines, including painkillers, in flood-stricken areas and the decline in production due to non-availability of raw products owing to inflation has doubled the aftermath of this calamity. It is of the utmost urgency to mitigate this crisis, as analgesics are the most commonly used over-the-counter medicines and constitute a whole tier of patient care. To get to the bottom of the problem there needs to be more research, analysis, and investigation executed at a national level on how to streamline the production, distribution and sale of medicine, on alternative sources of treatment and if possible the placement of subsidies so that the barrier to the consumer is reduced.